Haemolytic studies on Fish, Sheep and Human Blood Agar against Pathogenic Bacteria - Nadella, Ranjit Kumar; V. A., Minimol; Nilavan, Ezhil; Muthulakshmi, T.; Basha, K. Ahamed; Prasad, M. M. (Fishery Technology, 2020)
In this study, Î²-haemolytic activity of fish blood (Cyprinus rubrofuscus), sheep blood (SB) and human blood (HB) was assessed for studying haemolysis against reference bacterial strains Edwardsiella tarda (ATCC 15947); Aeromonas hydrophila (ATCC 35654); Enterobacter cloacae (ATCC 13047); Pseudomonas aeruginosa (ATCC 10145); Escherichia coli (ATCC 35218); Staphylococcus aureus (ATCC 43300); Vibrio cholera (MTCC 3906) and Salmonella paratyphii (ATCC 15305). Both human blood and fish blood showed similar Î²-haemolytic activity for all pathogens except E. cloacae on fish blood. The zone of haemolysis (mm) recorded in FB is 18, 28, 0, 22, 25, 14, 20, 22; in HB is 13, 15, 14, 23, 17, 18, 15, 17 and in SB is 14.6, 13.8, 15.8, 26.2, 19.4, 21.2, 17.6, 16.2 after 48 h respectively for E. tarda; A. hydrophila; E. cloacae; P. aeruginosa; E. coli; S. aureus; V. cholera and S. paratyphii. The present study also reports the antimicrobial property of fish blood against the commonly occurring fish pathogens. The result indicated a decrease in optical density readings in fish blood supplemented broth compared to control broth (without blood). This indicates clear inhibition of growth for the three pathogens in BHI broth supplemented with fish blood possesed due to the presence of antimicrobial substances in the fish blood. In conclusion, Î²-haemolytic activity observed better in FB plates when compared with HB plates and therefore, fish blood can be used as an alternative to sheep blood for haemolytic studies of fish pathogens.